Dieta del tiburón diamante Isurus oxyrinchus en el norte del Perú: Estudio preliminar - González-Pestana, Adriana; Córdova-Zavaleta, Francisco; Arrese-Dávila, Vania; Torrejón-Zegarra, Ruben; Acuña-Perales, Nicolas; Mangel, Jefffey C.; Alfaro-Shigueto, Joanna (Revista de Biología Marina y Oceanografía, 2022)
The shortfin mako shark (Isurus oxyrinchus) is considered one of the most important top predators in pelagic marine food webs. The diet of the shortfin mako shark was studied in northern Peru through the analysis of 25 stomach contents. Cephalopods were the most important prey group, followed by bony fishes and crustaceans. A total of 11 prey species were identified, with the Humboldt squid Dosidicus gigas being the most important prey, followed by the Ancistrocheirus lesueurii squid. The trophic level was 4.3 (tertiary predator) and the trophic niche width was 0.47 (intermediate degree of specialization). This study contributes to the limited knowledge about the ecology of the shortfin mako shark in northern Peru.